Outreach on the Use of Direct Cash Assistance (BLT) to Empower Low-Income Communities in Seberang Palinggam Village, Padang City - Chelsea Defista; Fadilah Permata Yora; Diva Nurfadhilah; Huriyatul Husna; Yulia Hanoselina (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
Poverty remains a serious challenge in Indonesia's national development, including in Seberang Palinggam Village, South Padang District, Padang City, which has been designated as one of the 23 slum settlement points in Padang City. The majority of its residents work as fishermen, port laborers, and small traders with unstable incomes, making them one of the most in need of social protection program interventions. This article aims to describe and analyze the implementation of socialization on the utilization of the People's Welfare Direct Cash Assistance (BLT Kesra) as an effort to empower the underprivileged community in the village. This research uses a qualitative approach with a descriptive method. Data were obtained thru observation, interactive discussions, documentation, and relevant literature studies. The research results show that before the socialization activities were carried out, the community's understanding of the objectives, distribution mechanisms, and utilization of the Kesra BLT was still limited. After the socialization was conducted in a participatory and communicative manner, the community's understanding increased, especially regarding the targeted, productive, and responsible use of the assistance. The socialization also succeeded in raising awareness that the BLT Kesra not only functions as short-term consumptive aid but also as a first step toward the economic independence of the community. However, the effectiveness of the program still faces challenges such as inaccuracies in recipient data and the lack of ongoing support. Therefore, socialization needs to be carried out periodically and integrated with skills training programs and business mentoring to create a more sustainable empowerment impact.